Teknologi Pembuatan Abon Ikan Lele Bebas Bau Amis (Penyuluhan dan Implementasi) - Ristina Siti Sundari; Andri Kusmayadi; Budhi Wahyu Fitriadi (Jurnal Pemberdayaan Masyarakat, 2021)
Almost people like any fishes, but some do not like the fish rancid even after processing. Catfish shredded is one of the processed processes. Turmeric, ginger, lemon, tamarind, vinegar, starfruit is often used to eliminate the fishy smell, but it still has taste left by itself. Community service was conducted to empower them and cope with the fishy smell problem. So that modified to the new variance beside the original product. Dan largen market share. Women Farmer Group for fisheries processing produces the object due to extension and implementation to adopt the technology innovation about catfish shredded processing to eliminate rancid on a fish odor. We hope this engagement and empowerment will become sustainable and spread out to other women farmer groups and animal products based on our research to raise economic circles. The group had a pre-test and post-test to measure the understanding and innovation adoption level. This engagement resulted in two variances of catfish by original and rancid free enriched with antioxidant of oregano leaf. The other result is that this new variance has more voluminous than the original in the same weight.